The Effect of Balanced Nutrition Education with ‘Gemar Bingo Card’ on Balanced Nutrition Knowledge and Junk Food Consumption Patterns in Overweight Adolescents - Patricia Sari, Vena; Purnamasari, Dyah; Rahmah, Hiya Alfi (Jurnal Riset Pangan dan Gizi, 2025)
Adolescents are one of the groups that are vulnerable to health problems. One of the health problems they experience is overnutrition. One of the factors causing overnutrition in adolescents is low knowledge of balanced nutrition and excessive consumption of junk food. Efforts to improve adolescent nutritional knowledge can be done by providing nutritional education using Gemar Bingo Card which is a combination of game cards and bingo games. The purpose of this study was to determine the effect of nutritional education with Gemar Bingo Card on knowledge and consumption patterns of junk food in overweight adolescents. The study used a quasi-experimental one group pre-test post-test method on 34 overweight adolescents at SMP Negeri 2 Purwokerto. The study was conducted 5 meetings. The variables were measured using a knowledge questionnaire and FFQ junk food consumption patterns. The variable analysis data was not normally distributed, so it was continued using the Wilcoxon Test. There was an increase in knowledge score from 16 to 20 after being given nutrition education with Gemar Bingo Card with a p value = 0.000. On the other hand, there was a decrease in the median score of junk food consumption patterns from 94.00 to 77.50 after being given nutrition education with Gemar Bingo Card with a p value = 0.004. There was an influence of balanced nutrition education by using Gemar Bingo Cards on knowledge of balanced nutrition and junk food consumption patterns.